Strategi Pemasaran Islami Terhadap Peningkatan Usaha Kripik Pisang Bunkey Makassar (Universitas Islam Negeri Alauddin Makassar, 2023)
This study aims to determine the marketing strategy and what obstacles occur in the process of increasing sales of the Bunkey banana chips business in Makassar. This research is in the form of qualitative using a phenomenological approach. Research data obtained from primary and secondary data. The instruments used in collecting the research data were observation guidelines, interviews, and documentation formats. The data obtained from the instrument were then analyzed using the Analytical Hierarchy Process (AHP) and tested using triangulation techniques. The research results obtained that 1). Bunkey's banana chips business applies Islamic marketing strategies, such as a) halal-labeled products; b) Using Islamic Advertising; c) Carry out promotional activities with 15% discount on Islamic holidays and 20% discount on the same date and month such as (10-10, 11-11, 12-12); d) Employees greet, behave politely and courteously when conducting transactions with consumers; and e) Doing marketing through its official website; 2). Bunkey's banana chips business also encountered several obstacles in increasing its business, such as: low brand awareness, relatively expensive shipping and export costs, and distribution channels that were still underdeveloped.